Nanocomposite coatings for hatching eggs and table eggs - Chekh Oleksandr (De Gruyter, 2021)
Theoretical and applied aspects of the concept of using biomimetic protective coatings GREEN ARTICLE (ARTIficial cutiCLE) in the poultry industry, namely in the production of table and hatching eggs, are developed. The basic matrix component of the protective coatings GREEN ARTICLE is chitosan, an environmentally friendly, inexpensive, and harmless material. It is experimentally proved that electrochemical and ultrasonic technologies for modifying a solution of chitosan in peroxide compounds (peracetic acid and hydrogen peroxide) with nanoparticles of oxides like titanium, iron, zinc, and metals, such as titanium, copper, and calcite, allow to create protective coatings of double action in accordance with the technologies: (a) extending the shelf life of table eggs, food green article (FGA) and (b) preventing contamination of hatching eggs with pathogenic microflora, increasing the hatchability of eggs, and the quality of chicken, hatching green article (HGA). In the technology of storing table eggs, artificial cuticles based on chitosan FGA are characterized by the following characteristics: increased thickness of 6–10 µm, low gas and moisture permeability, and high biocidal activity against pathogenic bacteria and viruses. It is shown that the use of FGA technology in the production of table eggs can extend the period of transportation and storage of products by 33–35 days at a temperature of 24°C and maintained a grade A (Haugh unit = 71–60) through the entire 35 days period. The technology HGA reduces the rate of contamination of hatching eggs with pathogenic microflora by 99.29–99.7%, while increasing the egg hatching rate by 2.3–11.6% compared to the control, depending on the cross of the poultry and the storage conditions of the hatching eggs. It is important that these technologies have a great prospect for application in countries that develop green technologies for the production of poultry products.